Atomically unraveling the dependence of surface microstructure on plasmon-induced hydrogen evolution on Au/SrTiO3. (January 2022) - Zeng, Bin; Wang, Shengyang; Feng, Zhendong; Xiao, Yejun; Li, Mingrun; Hong, Feng; Zhao, Yue; Feng, Zhaochi; Li, Rengui; Li, Can
Abstract: Strong light-matter interaction and coupled catalytic surface in plasmonic photocatalysts offer a unique opportunity for solar-to-chemical energy conversion. The interface/surface engineering is significant strategy to modulate the performance of plasmon-induced water splitting. This situation motivates the demand of a plasmonic heterostructure with well-defined atomic surface structures but identical bulk structure for plasmon-induced water splitting. In this work, using Au/SrTiO3 as a prototype, we found that altering the Ti-terminated and Sr-terminated surface of SrTiO3 gives rise to a remarkable difference in plasmon-induced hydrogen evolution activity. The efficiency of charge separation at the Sr-terminated surface is inferior compared with which at the Ti-terminated structure, while the reaction kinetics of Sr-terminated surfaces is faster than the counterpart, thus leading to a high plasmon-induced hydrogen evolution performance at Au/ SrTiO3 with surfaces of Sr-termination. Modulation of the interface/surface structure of Au/SrTiO3 changes not only charge separation but surface catalysis in plasmonic photocatalysts, where the catalysis process dominates the final photocatalytic performance. This work paves a way to design efficient plasmonic photocatalysts for solar-to-chemical energy conversion. Graphical Abstract: ga1 Highlights: Plasmonic heterostructures of Au/SrTiO3 with well-defined Ti-terminated and Sr-terminated surface structures were constructed. Hot electron injection and charge separation of Au/SrTiO3 is varied with different interface/surface structure. Au/SrTiO3 with Sr-terminated surface structure facilitates the kinetics of hydrogen evolution and shows higher hydrogen evolution activity than that of Au/SrTiO3 with Ti-terminated surface structure.